Rapid screening of a human genomic library in yeast artificial chromosomes for single-copy sequences. - Traver, C N (1989)
A yeast artificial chromosome (YAC) library in Saccharomyces cerevisiae consisting of 30,000 clones with an average insert size of 0.1 megabase pair of human DNA has been generated from primary fibroblast DNA. A YAC vector was modified to enable the recovery of both ends of a human DNA insert in plasmids in Escherichia coli and to confer G418 resistance to mammalian cells. A rapid method for yeast colony hybridization was used that exploits the ability of yeast spheroplasts to regenerate in a thin layer of calcium alginate. This method permits direct replica plating and processing of colonies from the primary transformation plate to nitrocellulose filters. Yeast colony hybridization conditions have been established to identify, within a YAC library of human genomic DNA, artificial chromosomes with homology to human DNA probes of unique single-copy sequence. An artificial chromosome with a 0.1-megabase-pair insert from the human Xq28 region has been identified by hybridization to a DNA probe that detects a unique sequence near the 3' end of the factor VIII gene.